Rediseño del sitio web del cuerpo de bomberos del cantón El Empalme provincia del Guayas, año 2015 - Ureta Limones, Mariuxi Maricela (2015)
In this research work it has developed dynamic responsive redesign of the Fire Department of the El Empalme City Guayas Province Website with the aim of publicizing this website. For the realization and fulfillment of this research project was analyzed and the use of new technology and web standard tools for creating dynamic and attractive interface with responsive design features, which allows viewing a website in different types of raised devices such as computers, tablets, Smartphone, presenting wide information about the Fire Department it is possible to obtain the due postulations record to applicants of the it. The dissemination website was made using social networks because people will attract the news of what happens inside and outside our country through them, they spread plugin using Facebook, Twitter YouTube and keeping active interaction with visitors, in addition to publicize them by means such as advertising posters detailing allowing emergency numbers, social networking and website. Persons accessing the website, will find a welcome screen to present facilities and work carried out by the Fire Department must then press the logo button that will link to the site home page, in the home screen you will find a navigation menu on new pages with full details in a dynamic and effective way. Finally concluded with the implementation of a hit counter website had a positive acceptance by the public, as hereby firefighter's body allows to present more about the institution, and increasing module records online volunteers, which will reduce time and help the environment. The redesign of interfaces dynamic and innovative way possible to keep the user's attention at all times of navigation, by having a simple and friendly interface without visual noise with the site. Keywords: Redesign, Design, Web Site Registration Module.